CHRONOTHERAPEUTIC DELIVERY OF DICLOFENACSODIUM USING ALMOND GUM AS CARRIER FOR THE TREATEMENT OF RHEUMATOID ARTHRITIS - K, RAJYALAKSHMI; Muzib Y, Indira; Ch, Saisree (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â  Â Objective: The objective of the present work was to develop and evaluate a matrix system for chronotherapeutic delivery of diclofenac sodium using almond gum as a carrier for the treatment rheumatoid arthritis. Methods: Matrix tablets of diclofenac sodium were prepared using 30, 40, 50, 60, and 70% w/w of tablet using almond gum as a carrier by wet granulation technique. These tablets were compression coated with Eudragit S100 to prevent drug release in the stomach. All formulations were evaluated for hardness, friability, weight variation, drug content, in vitro and in vivo studies. The release kinetics were studied. The almond gum was characterized by viscosity measurements and Fourier transform infrared spectroscopy (FTIR) analysis. The coated (FC1 to FC5) and uncoated tablets (F1 to F5) were evaluated for in vitro release of diclofenac sodium after sequential exposure to pH 1.2, pH 7.4, and pH 6.8, respectively, for 2 hr, 3 hr, and 19 hr in the absence as well as presence of rat cecal content. The selected formulation was subjected to in vivo targeting efficacy studies by roentgenography technique. Results: In vitro release studies indicated that the matrix tablets (F1 to F5) failed to control the drug release in the physiological environment of the stomach and small intestine. On the other hand, compression-coated formulations were able to protect the tablet cores from premature drug release. In the presence of rat cecal contents, FC5 formulation has shown highest release for longer period when compared to that of FC5 in the absence of cecal contents. The values of the correlation coefficient indicated that the drug release followed zero order drug release kinetics with Peppas drug release mechanism. FTIR studies confirmed that there was no interaction between the drug and the carrier. X-ray studies confirmed that the tablet successfully reached colon without getting disintegrated in upper gastrointestinal tract. Conclusion: Based on the results, selective delivery of diclofenac sodium to the colon could be achieved using 70% w/w (FC5) of almond gum matrix tablets compression coated with Eudragit S100 as a carrier. Keywords: Diclofenac sodium, Gum almond, Eudragit S100, Roentgenography, Rat cecal content.